Does anaerobic digestion really help to reduce greenhouse gas emissions? A nuanced case study based on 30 cogeneration plants in France. (15th January 2023) - Malet, Nicolas; Pellerin, Sylvain; Girault, Romain; Nesme, Thomas
Abstract: Anaerobic digestion (AD) is often regarded as a promising option to substitute fossil fuel by renewable energy from biomass while sequestering carbon in soils through digestate spreading. Many studies have quantified the net greenhouse gas (GHG) emissions of AD plants. However, GHG assessments are often based on system delimitation that is not always comprehensive enough, leading to incomplete GHG budgets. This is especially the case for the baseline to which AD is compared. In this paper, we propose a thorough evaluation of the net GHG emissions of 30 cogeneration plants in France compared to a detailed definition and assessment of their related baseline, the latter being mostly based on direct biomass supply to agricultural soils. GHG emissions were quantified (i) from substrate supply to AD plants until the use of the produced heat and electricity and to the agricultural use of the produced digestate for the AD scenario and (ii) from substrate supply to their application on agricultural soils for the baseline scenario. Our results showed that on average, in the French energy context, AD plants do not provide significant GHG mitigation benefits, partly because fossil fuel substitution is offset by lower carbon storage in soils compared to the baseline. However, we also found large variability among AD plants in difference in net GHG emissions between both scenarios, a third of which are effective from a GHG mitigation perspective. This variability was contributed by (i) the efficiency of soil carbon storage in the baseline; the lower it is, the more AD displays interest for mitigating GHG emissions; and (ii) the efficiency of AD management, especially emission avoidance by digestate covering, leakage control and heat recovery. Additionally, based on a sensitivity analysis, we showed that direct injection would perform better than cogeneration, and that AD would better attenuate net GHG emissions in a European energy context rather than in the highly decarbonised French context. Finally, we showed that the implementation of optimal management of AD plants could significantly improve net GHG emissions from biogas production. This study highlighted the need for careful assessment of AD based on a rigorous definition of the baseline against which AD climate mitigation performances are compared. Highlights: GHG assessment of 30 anaerobic digestion plants in France. Anaerobic digestion systems were compared to a carefully evaluated baseline. On average, the 30 plants did not mitigate GHG emissions more than the baseline. One third of the AD plants exhibited a GHG mitigation effect. Variability was driven by soil carbon storage efficiency and AD management practices.